Functional characterization of peripheral blood dendritic cells and monocytes in systemic lupus erythematosus - Henriques, A (2011)
With the purpose of contributing to a better knowledge of the APCs functional activity in SLE, we evaluated the distribution and functional ability to produce pro-inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-12) of peripheral blood (PB) monocytes and DC (tDC), particularly myeloid (mDC) and CD14(-/low)CD16(+) DC subpopulations comparing them with those obtained from healthy individuals. The study was performed in 34 SLE patients with diverse disease activity scores (SLEDAI) and 13 healthy age- and sex-matched controls (NC). Our results show an overall decrease in absolute number and relative frequency of tDC in SLE patients with active disease when compared to those with inactive disease and NC, although this decrease did not seem to have an effect on the distribution of PB DC subsets. The monocytes number in SLE patients was similar to those found in NC, whereas a higher frequency of monocytes producing cytokines as well as the amount of each cytokine per cell found without stimulation was particularly observed in those patients with active disease. After stimulation, we observed a higher frequency of IL-12-producing monocytes in active SLE patients. On the other hand, we found among DCs higher frequencies of cytokine-producing CD14(-/low)CD16(+) DCs and a higher amount of cytokines produced per cell, particularly in active disease. These findings support an increased production of inflammatory cytokines by APCs in active SLE, mostly associated with alterations in CD14(-/low)CD16(+) DC subset homeostasis that might contribute to explain the dynamic role of these cells in disease pathogenesis